EFFECT OF COMPANY VALUE, LEVERAGE, AND COMPANY SIZE ON PROFIT PERSISTENCE IN JAKARTA ISLAMIC INDEX (JII) LISTED COMPANIES - Budi Prasetyo; Satiti Utami; Alwazir Abdusshomad; Mukti Wijaya; Nawang Kalbuana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study was to determine the effect of Company Value, Leverage, and Company Size on Earnings Persistence in Companies Listed in the Jakarta Islamic Index (JII). Data obtained from the page www.idnfinancial.com. The data in this study are secondary data. The approach used in this research is a quantitative approach. Sampling technique using purposive sampling technique and data analysis using multiple linear regression analysis. Samples that fit the criteria were obtained by 23 companies during the 2015-2019 observation period. Then the data were analyzed using the SPSS data regression analysis model.26.0 The results showed that firm value had no significant effect on earnings persistence, leverage and firm size had a significant effect on earnings persistence on companies listed on the Jakarta Islamic Index (JII) for the 2015-2019 period.